Hubungan Pengetahuan Ibu, Dukungan Keluarga, dan Dukungan Petugas Kesehatan dengan Pemberian ASI Eksklusif - Ketut Catur Anggarwati; Anna V.Pont; Rafika Rafika; Masudin Masudin (Politeknik Kesehatan Kemenkes Mamuju, 2019)
ABSTRACT Breast Milk contains antibody-rich colostrum because it contains high immune proteins and germ killers so exclusive breastfeeding can reduce infant mortality. Exclusive breastfeeding achievement in Mamboro Community Center in 2015 was 118 (71.95%) and 2016 decreased by 183 (62%). Factors that cause the baby not to get exclusive breastfeeding include education, knowledge, values ​​or cultural customs, family support and support of health workers. The purpose of this research is to know the relationship of mother's knowledge, family support and support of health officer with exclusive breast feeding in Posyandu working area of ​​Mamboro Community Health Center. This research use analytic survey method withapproach cross sectional, data collecting using primary data is by filling questionnaires on mothers who have infants aged 6-12 months, research conducted on 14 April to 16 May 2018. Sampling technique is purposive sampling with inclusion and exclusion criteria with a total sample of 55 respondents. Analysis of bivariate data usingstatistical test Chi Square with 95% confidence level (α = 0,05). The result of statistic test showed that the relationship of mother's knowledge with exclusive breastfeeding was obtained p value of 0,04 (p value <0,05), relation between family support and exclusive breastfeeding was obtained p value 0,333 (p value>0,05) and the relationship between health care support and exclusive breastfeeding was obtained by p value of 0.40 (p value>0.05). In conclusion there is a relationship between mother knowledge with exclusive breastfeeding in Posyandu work area of ​​Mamboro Community Health Center. Trying to educate and increase knowledge Mother'sabout exclusive breastfeeding, do counseling during exclusive breastfeeding period and always involve husband in giving related information about ASI. Keywords : exclusive breastfeeding, knowledge, family support, health officer support